E-government and environmental sustainability: results from three Australian cases. (14th January 2008) - Haigh, Nardia; Griffiths, Andrew
In this study, we bring Information Systems (IS) and environmental sustainability together to examine the environmental sustainability of implementing Electronic Government (e-government). Results indicate that while positive environmental outcomes were sought in high-level strategies, they dissipated as they made their way down to the e-government strategy level. We analyse four strategy layers; showing the extent to which strategic intent can become diluted layer by layer, and develop an environmental perspective by which to analyse IS that highlight previously overlooked inefficiencies. We contribute to the stream of thought combining IS with environmental sustainability and discuss the implications for practitioners and researchers.